The Evolution of the Service Sector in the Context of Romania’s Accession to the European Union - Marius PROFIROIU; Tudorel ANDREI; Alina PROFIROIU; Stelian STANCU (Transylvanian Review of Administrative Sciences, 2008)
The article aims to identify the characteristicsof the evolution of the service market in Romaniabetween 1993 and 2006. The development of theservice market will become an important factor forthe economic development of Romania and forits integration in the European structures in thefollowing years. During the transition period theservice sector faced substantial changes regardingthe type of services provided, the features of thecompanies providing services etc. The presentstudy uses statistical data made available by theNational Institute of Statistics starting with July 2008.